2014
DOI: 10.4269/ajtmh.14-0260
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum B-Cell Activating Factor Levels During Visceral Leishmaniasis

Abstract: Abstract. Elevation of serum B-cell activating factor (BAFF) is one of the characteristics of immunological disorders, including autoimmunity, but the levels of BAFF in infectious diseases have not been studied well. Here, we showed the elevation of serum BAFF in patients with visceral leishmaniasis (VL). The mean serum BAFF value in VL patients (4.65 ng/mL) was 4.3 times higher than that of healthy controls (1.08 ng/mL), and 90% of VL patients showed serum BAFF above the cutoff that was calculated as the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…3). The significance of BAFF in infected humans is not as clear as animal models suggest, because patients with visceral leishmaniasis also manifest elevated serum BAFF levels, but a correlation with serum IgG levels was not found (166). In the same study, a second group of patients with Chagas' disease did not have elevated serum BAFF or increased IgG levels.…”
Section: Parasites Leishmaniasis and Chagas' Diseasementioning
confidence: 89%
“…3). The significance of BAFF in infected humans is not as clear as animal models suggest, because patients with visceral leishmaniasis also manifest elevated serum BAFF levels, but a correlation with serum IgG levels was not found (166). In the same study, a second group of patients with Chagas' disease did not have elevated serum BAFF or increased IgG levels.…”
Section: Parasites Leishmaniasis and Chagas' Diseasementioning
confidence: 89%
“…Therefore, it is possible that marked changes in cytokine/chemokine levels during malaria [51][52][53], as well as Plasmodium immune-modulatory molecules [38] drive BAFF/APRIL production by these cells. In the recent years, many research articles have reported a role for BAFF/APRIL system in the pathogenesis of autoimmune and infectious diseases [23,26,[31][32][33][34][35], including malaria [35,36,54]. However, while there is some evidence that BAFF plays a role in determining the outcome of P. falciparum malaria, nothing is known about the role of the follows: 1) APRIL in any malaria or 2) BAFF/APRIL system in P. vivax malaria.…”
Section: Malaria Is Characterized By Many Pathophysiological Changes mentioning
confidence: 99%
“…The APRIL and/or BAFF plasma levels are upregulated in many noninfectious [26,[68][69][70][71][72][73][74][75][76] and infectious diseases [32,73,77,78], including malaria [36,54] that are often accompanied by polyclonal B-cell activation, hypergammaglobulinemia, autoimmune disorders and lymphopenia. In malaria, polyclonal B-cell activation has been shown in the acute phase of P. vivax and P. falciparum malaria [15], which decreases 5-15 days after the beginning of treatment [15], with similar transient kinetics of IL-10, APRIL and/or BAFF levels, observed in our study.…”
Section: Malaria Is Characterized By Many Pathophysiological Changes mentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway strictly requires IFN‐I signaling , which seems to be necessary for enhancing antibody production. Elevated levels of B cell activating factor BAFF were also proposed as another possible mechanism . Interestingly, T follicular helper cells (TFh) do not seem to play a role in the induction or maintenance of hypergammaglobulinemia .…”
Section: Introductionmentioning
confidence: 99%